Effects of Trypanosoma vivax infection during pregnancy on feed intake, nitrogen retention and liveweight changes in West African Dwarf ewes - Akinbamijo, O.O.; Reynolds, L.; Gort, G. (Cambridge University Press, 1994)
The effects of infection with T. vivax in mid- or late pregnancy on food intake and utilization, liveweight changes, abortion rate and lamb growth rate were investigated in West African Dwarf ewes at Ibadan, Nigeria in 1990. Rate of livewight gain by ewes infected during mid-pregnancy (IMH) was 16g/day compared with 33 and 37g/day for the uninfected ewes offered medium (CM) or high (CH) plane diets. Although digestibility coefficients were not affected, intake of digestible organic matter was higher in CH ewes than in IMH and CM ewes. Nitrogen retention at mid-pregnancy on a metabolic size basis was higher in CH ewes than in CM and IMH ewes. Lamb birth weight and survival rate were lower in infected ewes. Ewes infected in mid-pregnancy (IMH) and in late pregnancy (ILH) had mean birth weights of 1.4 and 1.0 kg compared with CM and CH ewes, which had mean birth weights of 1.9 and 2.0 kg respectively. Observed survival rates were 63,15,75 and 80 percent for lambs nursed by IMH, ILH, CM, and CM ewes respectively. During the first 6 weeks postpartum, lambs growth rate in all groups did not differ. However, during weeks 7-12 postpartum, lambs nursed by IMH ewes had significantly lower growth rates. Weaning weight was also lower in lambs from IMH (5.0 kg) dams than in lambs from CM and CH dams (7.1 kg). Infection during late pregnancy was more severe and all infected ewes lost weight due to reduced feed intake and fever. T. vivax infection in sheep is responsible for reproductive wastage, abortion, poor lamb growth and ewe mortality.